2022
DOI: 10.1097/sla.0000000000005413
|View full text |Cite
|
Sign up to set email alerts
|

Vein Bypass Versus Nitinol Stent in Long Femoropopliteal Lesions

Abstract: Objectives: The aim of this study was to compare technical success, patency rates and clinical outcomes of vein bypass (VBP) with angioplasty and nitinol stents (NS) in femoropopliteal Trans-Atlantic Intersociety Consensus (TASC) II C and D lesions. Summary Background Data: Guidelines widely recommend an endovascular-first strategy for long femoropopliteal lesions without sufficient data comparing it with vein bypass surgery. Methods: A single-center prospective, randomized controlled trial (RCT) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…16 Since the publication of this metaanalysis, 4 additional randomized controlled trials using a strategy with stent implantation have been performed. [5][6][7][8][9] These studies found similar primary 1.…”
Section: Femoropopliteal Artery Revascularizationmentioning
confidence: 62%
See 3 more Smart Citations
“…16 Since the publication of this metaanalysis, 4 additional randomized controlled trials using a strategy with stent implantation have been performed. [5][6][7][8][9] These studies found similar primary 1.…”
Section: Femoropopliteal Artery Revascularizationmentioning
confidence: 62%
“…Whereas in the past, BSx has been regarded as the standard of care 13 and remains indicated especially in patients with complex disease, 10-12,14 notable advancements in the EVT armamentarium and technique, including the introduction of stent implantation over the past decades, have resulted in promising evidence suggesting similar primary patency rates in EVT vs BSx. 5,7,9,15 With respect to clinical endpoints, the BASIL (Bypass Versus Angioplasty in Severe Ischemia of the Leg) amputation-free and overall survival rates were found in the BSx group. 16 The inclusion of observational studies and studies not using a strategy with stent implantation limit the applicability of these findings to contemporary endovascular practice.…”
Section: Femoropopliteal Artery Revascularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Die von Farhan et al veröffentlichten 24-Monats-Daten nach endovaskulärer oder offen chirurgischer Therapie von Oberschenkelläsionen zeigte keine Differenz in Bezug auf die MAE-Rate (40,1 % vs. 36,4 %; p = 0,447) oder das amputationsfreie Überleben mit 88,1 % vs. 90,0 % (p = 0,455) bei einer signifikant niedrigeren Komplikationsrate (6,8 % vs. 22,6 %; p < 0,001) zugunsten der endovaskulären Versorgung [23]. Sogar nach 4 Jahren Nachbeobachtungszeit konnten die angewendeten Stentverfahren im Oberschenkel Ergebnisse aufweisen, die hinsichtlich der Beinerhaltungs-und MAE-Rate keinen Unterschied zum Venenbypass zeigen [24]. Eine Kostenanalyse hinsichtlich der Implantate liegt nicht vor.…”
Section: Diskussionunclassified